Clinical, biochemical, endoscopic and histopathological evaluation of biological treatment in ulcerative colitis: Evaluación clínica, bioquímica, endoscópica e histopatológica del tratamiento biológico de colitis ulcerativa - López-Bernal, Carlos A. (2022)
Background: Biological treatment is currently used as an alternative for the treatment of ulcerative colitis in patient’s refractory to conventional treatment. Objective: To evaluate biological treatment in patients with ulcerative colitis refractory to conventional treatment in a 3rd level care Hospital. Methods: A descriptive, retrospective, longitudinal study was carried out in patients with UC who were refractory to conventional treatment and who received biological treatment. The variables were evaluated in 3 moments: basal state (without biological treatment), at six and twelve months from the start of biological treatment. Descriptive statistics were used to characterize general population, later the 3 states mentioned above were described with their respective variables. Results: Eighteen patients with a mean age of 41.2 years were included. Evaluations at baseline and at 6 and 12 months showed: presence of blood in stools and abdominal pain in 94.4%%, 22.2% and 11.1% respectively; hemoglobin concentration >10.5 g/dl in 50%, 83.3% and 88.9%; serum albumin concentration >3.2 g/dl in 72.2%, 83.3% and 88.9%; the visual Mayo endoscopic scale 38.9%, 33.3% and 16.7% presented Mayo 2 and 61.1%, 16.7% and 1.7% Mayo 3. The histological activity in the baseline evaluation reached a severe level (11.1%), while in evaluations at 6 and 12 months they reached moderate in 55.6% and 27.8% respectively. Conclusions: Biological therapy as a treatment in patients with ulcerative colitis showed improvement in clinical, biochemical, endoscopic and histological manifestations, so far none with deep remission of the disease, no adverse reactions to treatment have been presented.